Anti–Cyclic Citrullinated Peptide Antibodies Correlate to Ultrasound Synovitis in Rheumatoid Arthritis Better Than C-Reactive Protein. Issue 8 (29th December 2021) - Lu, Cheng-Hsun; Chen, Lung-Fang; Huang, Yi-Min; Cheng, Chiao-Feng; Hsieh, Song-Chou; Li, Ko-Jen
Abstract : Objectives: The aim of this study was to compare ultrasound (US) grading and laboratory measures in patients with rheumatoid arthritis. Methods: Two-hundred four patients with rheumatoid arthritis who received US evaluation for synovitis were included after excluding those using tocilizumab. Ultrasound grading of synovial hypertrophy (SH) and power Doppler (PD) at the most severe site were recorded. An assessment of the correlation of laboratory measures and US grading was conducted by reviewing the electronic medical records. Results: High-titer anti–cyclic citrullinated peptide (anti-CCP) antibodies positivity was associated with SH grade ≥2 (odds ratio [OR], 6.00; 95% confidence interval [CI], 1.78–20.2) and PD grade ≥2 (OR, 5.56; 95% CI, 1.82–16.9). Recent C-reactive protein (CRP) levels ≥0.3 mg/dL were associated with SH grade ≥2 (OR, 3.13; 95% CI, 1.38–7.10) and PD grade ≥2 (OR, 2.38; 95% CI, 1.31–4.31). Anti-CCP antibody levels correlated with US scores better than the levels of CRP with higher Spearman ρ correlation coefficients. Most of the patients with recent CRP levels <0.3 mg/dL had US synovitis. In logistic regression, high levels of anti-CCP antibodies and CRP were both independently associated with SH grade ≥2 and PD grade ≥2. Conclusions: Higher levels of anti-CCP antibodies and CRP may predict synovitis on US, whereas discrepancies existed between inflammatory markers and US grading. These findings suggest that US has a role in the comprehensive assessment of disease activity, especially for patients with high-titer positive anti-CCP antibodies.